Access and permanence of the learner with autism in Brazil: legal theoretical frameworks that subsidize this right (Research, Society and Development, 2020)
The respective work has the objective of understanding the process of constructing the scholastic inclusion of the student with Autistic Spectrum Disorder (TEA), as well as its definition. We will focus on the documents that are the legal and normative frameworks about special education. As well as, in the theoretical references that investigate the issue of Autistic Spectrum Disorder and its inclusion in mainstream schools. The qualitative research was adopted to better understand and deepen the discussion about the objective in question. Seeking to understand the school reality and the subject inserted in it, especially the learner with TEA, a right guaranteed in legal provisions. In this sense, the organization of support measures that provide opportunities for the implementation of collaborative education networks, which aim to offer structural conditions at the school level, will have the possibility of establishing a solid process for building day-to-day school inclusion. According to our studies, we point out the following result: the involvement of the school, family and education professionals in the organization of inclusive pedagogical practices lead to the expansion of cognitive structures, will facilitate learning in the various areas of knowledge, also helping not only in the intellectual development of the learner with TEA, but also in promoting their autonomy and social well-being, and contributing in a productive way to their access and permanence in common education.